Geochemical dispersal in till: Waterford area, New Brunswick - Munn, M.; Broster, B.; Pronk, A. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
Geochemical analyses of tills in the Waterford area indicate that till matrix closely reflects underlying bedrock. This is likely due to: (1) efficient glacial entrainment of local bedrock material, (2) limited transport distances, and (3) limited mixing prior to deposition as till. Dispersal patterns of chemical elements show elongated dispersal patterns parallel to south-southeastward ice-flow directions. Small (up-ice) source areas with unique lithology that lie at relatively high elevations impart readily identifiable geochemical dispersal trains. Train lengths generally vary from 2 km to about 8 km, but can be up to 18 km long for some elements. Dispersal patterns for till geochemistry are of similar size and shape to those found previously for till clasts, although extensive pre-glacial erosion and weathering of some friable mafic Hthologies of the Mechanic Settlement Pluton has resulted in larger geochemical dispersal patterns relative to the dispersal pattern for mafic till clasts. Our results confirm that, in New Brunswick, a 2 km sampling interval is effective for identification of significant geochemical anomalies in till matrix.